2008
DOI: 10.1086/588827
|View full text |Cite
|
Sign up to set email alerts
|

Oral and IntestinalCandidaColonization in Patients Undergoing Hematopoietic Stem‐Cell Transplantation

Abstract: We investigated (1) the prevalence and quantity of, as well as risk factors for, orointestinal Candida colonization in patients undergoing hematopoietic stem-cell transplantation (HSCT) and (2) the genetic relatedness of colonizing C. albicans strains. Mouth-wash and stool samples were collected from 77 patients before they underwent HSCT and on days 1, 8, and 15 and were quantitatively cultured. C. albicans isolates were genotyped by microsatellite-marker analysis. The prevalence and quantity of orointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 12 publications
1
17
1
1
Order By: Relevance
“…albicans can be isolated from the mouth of most individuals, but the fungus causes oral disease such as oral mucositis in primarily immunocompromised individuals [45-47]. Further, Candida albicans is seen as a reservoir for pneumonia [48] and intestinal related diseases [49]. …”
Section: Discussionmentioning
confidence: 99%
“…albicans can be isolated from the mouth of most individuals, but the fungus causes oral disease such as oral mucositis in primarily immunocompromised individuals [45-47]. Further, Candida albicans is seen as a reservoir for pneumonia [48] and intestinal related diseases [49]. …”
Section: Discussionmentioning
confidence: 99%
“…Pathogens that use the gastrointestinal tract reservoir as their primary site of colonization, such as Pseudomonas aeruginosa and Candida albicans , carry the highest case fatality rates when they disseminate and cause subsequent infection [1], [2], [3], [4], [5], [6], [7]. In addition there is increasing evidence that many patients enter the hospital as carriers of these pathogens in their stool as a result of chronic overuse of antibiotics [8], [9], [10], [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Zollner-Schwetz et al, believed that gastrointestinal tract colonization by Candida species in neutropenic patients is an important risk factor for invasive candidiasis. They also found that 48% of multi-colonized patients had same Candida species in their oral and intestinal samples (24). …”
Section: Discussionmentioning
confidence: 99%